InMI and its potential originality – musical creativity in composers’ minds - Copeland, Natalia E. (Interdisciplinary Studies in Musicology, 2019)
The current article explores the potential innovativeness of Involuntary Musical Imagery and presents the current state of InMI researches. There is a lack of precise definition of the term, as well as related terms (such as earworm or musical imagery). InMI is often equated to earworms which does not do justice to its creative potential. Several authors suggest that InMI can be a source of new melodies useful for composers in their composition process. The article proposes that InMI can consist of new melodies and appear as a single event. Composers use their working memory and musical abilities to volitionaly loop the tune in their head, then transcribe it into external realm (notation, recording). Composers can later use it in their creative process. The use of InMI in composing is a matter of individual differences between composers.